(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2020)
T0001 is the first mutant of etanercept with a higher affinity to tumor necrosis factor α (TNF-α) than etanercept. In order to investigate the safety and tolerability of T0001, a study was carried out in healthy Chinese subjects. A first-in-human, dose escalation study was conducted in healthy Chinese subjects. Fifty-six subjects were divided into six dose cohorts (10 mg, 20 mg, 35 mg, 50 mg, 65 mg and 75 mg) to receive a single subcutaneous injection of T0001. Safety and tolerability assessment were based on the records of vital signs, physical examinations, clinical laboratory tests, 12-lead electrocardiograms and adverse events (AEs). All subjects were in good compliance and none withdraw due to AEs. No serious AEs occurred. A total of twenty-three AEs in sixteen subjects were recorded, and eighteen of these AEs were believed to be related to T0001. The most frequently reported AEs were injection site reactions and white blood cell count increase. All these AEs were of mild to moderate intensity and most of them recovered spontaneously within 14 days. In this study, no dose-limiting toxicity was observed, and the maximum tolerated dose was identified as 75 mg. T0001 was considered safe and generally well tolerated at doses up to 75 mg in healthy Chinese volunteers.